Some aspects of the theory of referendum (Journal of actual problems of jurisprudence, 2018)
The article is devoted to the analysis of one of the most important, interesting and requires a rethinking of the forms of direct democracy – a referendum. The referendum is defined as a national survey, a nationwide vote on the bill What are the specifics of this form of direct democracy? What explains the flurry of activity and its application in popularity in the early 21 th century, and especially in recent years.Key words: referendum, popular consultation, plebiscite, the constitution, the referendum mechanism.